Coronary artery fistula detected with transesophageal echocardiography: An unexpected cause of pulmonary hypertension and chest pain. Issue 12 (16th October 2018) - Erdogan, Emrah; Cap, Murat; Topel, Cagdas; Efe, Suleyman C.; Gurbuz, Ahmet S.
Abstract : Coronary artery fistulae are congenital cardiac abnormalities characterized by an abnormal communication between a coronary artery and a cardiac chamber, systemic or pulmonary vessel. Most of the cases are asymptomatic and are discovered incidentally during an angiography. We describe a rare case of a right coronary artery fistula draining to the right atrium, manifesting in chest pain and pulmonary arterial hypertension (PAH). The fistula was detected on transesophageal echocardiography during the workup for PAH.